No Sympathy for the Devil: The Guise of the Good Defended - (:unkn) unknown (My University, 2020)
At the intersection of action theory and value theory is a provocative thesis: the Guise of the Good. The Guise of the Good (GG) states that whenever an agent acts intentionally, she sees some good in her action. Thus, according to GG, positive evaluation is essential to the nature of intentional action. Kieran Setiya (2010), however, argues that it is possible to act intentionally without believing that there is any reason to count in favor of one’s action: if intentional action is action for a reason, says Setiya, then the Guise of the Good is false. But I argue that Setiya’s account is insufficiently sensitive to the relationship that agents bear to their own prospective actions. I argue that this relationship is inherently normative and that, consequently, the Guise of the Good is true.
Keywords: action theory; Guise of the Good; intention; metaethics; value theory